Effect of Goodwill Value Toward Firm Value - Antoni Antoni; Kurniawan Arif Maspul; Lena Ellitan; Siti Nuridah; Fudji Sri Mar'ati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research aims to contribute to filling a significant gap by studying changes in the value of mining companies' goodwill, this study highlights the focus of research on companies that report positive goodwill values will then be considered to have high intellectual capital, so investors assume the company has better earning potential in the future. This research sample consists of mining companies listed on the Indonesia Stock Exchange in 2018-2020. The analysis techniques used linear regression analysis are simple. The results of simple linear r egression analysis in this study indicate that the value of goodwill has no effect on firm value.